Effects of Heat-Stress on Oocyte Number and Quality and In Vitro Embryo Production in Holstein Heifers - Çizmeci, Sakine Ülküm; Dinç, Dursun Ali; Yesilkaya, Omer Faruk; Çiftçi, Muhammed Furkan; Takcı, Abdurrahman; Bucak, Mustafa Numan (Acta Scientiae Veterinariae, 2022)
Background: This study aimed to determine the effects of environmental temperature on the number and quality of oocytes and embryo production rates obtained by performing ovum pick up (OPU). Heat stress leads to long-term, short-term, visible, and invisible effects in dairy cows. Its effects on reproduction are evident in all stages, from oocyte development to birth. Disturbance in ovarian follicle development, follicular dominance deficiency, anoestrus, polyspermia, embryonic losses, decreased fetal growth, and abortion are some examples of responses to these effects. The aim of the present study was aimed to determine the effects of ambient temperature on oocyte quality and number and embryo production rates. Materials, Methods & Results: The animal material used in this study comprised 10 Holstein heifers. At the beginning of the study, the heifers were 13-15 months old. OPU was performed at different times of the year, and weather conditions were recorded. Grouping according to ambient temperature was done as < 10°C (group 1), 10-25°C (group 2), and > 25°C (group 3). The veterinary ultrasonography device and a set of compatible intravaginal OPU probe, catheter, and aspiration device were used for OPU application. All antral follicles with diameters of 2-8 mm in the ovaries were aspirated. The aspirated follicle fluids were examined under a stereo microscope, and the cumulus-oocyte complexes (COC) were collected and classified according to their structure. A, B, and C-quality oocytes were included in the in vitro embryo production process. After performing 69 OPUs on random days of the cycle, the number of oocytes per OPU was found to be 8.72, 6.32, and 6.85 in groups 1, 2, and 3, respectively (P < 0.05). The number of viable oocytes per OPU was 6.83, 4.64, and 4.65 in groups 1, 2, and 3, respectively (P < 0.05). The statistical difference between the first group and the other groups was significant for cleavage and blastocyst counts (P < 0.05). Discussion: All the negative effects of heat stress on animals resulted from the increased body temperature. Reproductive performance is adversely affected by high temperatures and humidity during periods of high ambient temperatures. Metabolic heat is released, and the heat load increases due to the metabolism of nutrients in cattle. Internal body temperature is regulated via the dissipation of metabolic heat to the environment. The amount of heat dissipated via conduction and convection depends on the unit body weight, surface area, skin and coat color, difference in temperature gradient of the animal and ambient temperature, and humidity. In the present study, it was determined that the blastocyst development rates of the oocytes obtained in the warm season (>25°C [group 3]) were lower than those of the other groups. It was concluded that this may be because the oocytes developed under chronic heat stress in the animals, and several cycles were required to enhance oocyte quality and developmental potential. Additional studies are needed to investigate the response of oocytes obtained with OPU to heat stress during embryonic developmental stages and to determine the sensitivity and effects of embryonic tissue damage according to developmental stages. Based on the results of the present study, it was concluded that performing OPU and in vitro embryo production (IVEP) when the ambient temperature is close to the thermoneutral limits may increase the blastocyst development rates. Keywords: blastocyst, heat stress, heifer, in vitro embryo production, oocyte quality, ovum pick-up.